ESTRABÃO E A ENUNCIAÇÃO DE UMA "ESTRUTURA DE ATITUDES E REFERÊNCIA DA CULTURA IMPERIAL" - Mendes, Norma Musco (PHOÎNIX, 2020)
This paper aims to demonstrate how the space and time contexts are united in the socio-physical entity of the human body, through the analysis of the meaning of dressing the toga.